Impact of inlet slug flow on horizontal gas-liquid separator - Lee, Siong Hoong (2019)
This study has demonstrated that the current sizing criteria for a gas-liquid separator commonly used in the industry maybe inadequate. The sizing criteria has not taken into account the inlet flow pattern and fluid hydrodynamics inside the separator. In this study, the inlet flow pattern was showed to have significant impact in the separator sizing and the fluid hydrodynamics inside the separator. The experiment was conducted using a test rig consists of a horizontal gas-liquid separator operating at 45 °C. The liquid was constantly fed at 430 mL/min while the gas flowrate was adjusted to meet the requirement of inlet momentum from 200 to 2500 Pa. The liquid and gas phase used in the experiment were water and air, respectively. Experimental results demonstrated that the inlet flow was slug flow for inlet momentum of 200 to 1500 Pa, and the Mandhane’s map could be used to predict the flow pattern Computational Fluids Dynamics (CFD) has demonstrated its function as an essential tools to simulate hydrodynamic inside the separator. However, the standard approach for Volume of Fluids (VOF) does not able to model the hydraulic jump in the inlet slug flow and additional User Define Function (UDF) using normal distribution equation was used at the inlet boundary to simulate the hydraulic jump. Another advantage was demonstrated using CFD in this study is the complex calculation such as kinetic energy of turbulence can be solved easily. Realizable k-ε turbulence model has provided good agreement with experimental result and is recommended for this type of application. At inlet momentum of 800 Pa and lower, the sloshing does not occurred in the separator and the Souders-Brown constant from the guidelines is still valid for gas phase section sizing for horizontal gas-liquid separator which provided acceptable low level liquid carryover at gas phase. For inlet momentum of 1000 Pa and higher, the impact of inlet slug flow initiated the separator sloshing phenomena. Sloshing was found to increase the liquid carryover in the gas phase. Kinetic energy of turbulence at liquid phase shall be kept below 15 m2/s2 to avoid any sloshing in the separator. The sloshing phenomena in the separator can be avoided by lowering the liquid level in the separator which is a very economical approach in retrofitting gasliquid separator and to avoid expensive separation internals. Additional recommended liquid level from this study was suggested in the gas-liquid separator sizing in order to mitigate the sloshing phenomena in the separator.